Embedding the AMPLE in a CGE model to analyze intersectoral and economy-wide policy issues - Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2016)
This study implements an updated set of projections for Philippine agriculture, which addresses the following key issues: (1) the proper modeling of land allocation to better analyze the implications of land scarcity under climate change; (2) the impact of climate change, agricultural productivity growth, and trade liberalization on agriculture; (3) the indirect impacts of climate change and agricultural productivity growth on the rest of the economy; and (4) the impact of productivity growth in manufacturing and services on agriculture, including on agricultural wages. To address the first and second issues, the study provides a new approach toward modeling land allocation, and updated projections for agriculture to 2030 using the extended Agricultural Model for Policy Evaluation (AMPLE). The study will address the third and fourth issues by extending AMPLE into a computable general equilibrium (CGE) version, called AMPLE - CGE, which is still being developed. This report documents the compilation of the AMPLE - CGE data set, namely, the 2013 Social Accounting Matrix.
Keywords: 330; Area allocation; quasi-fixed factor; partial equilibrium model; constant elasticity of transformation